Musculoskeletal pain and quality of life in patients undergoing hemodialysis: a single-center study - Ersoy Yeşil, Ezgi; Pehlivan, Özlem; Toprak, Zeki; Kayabaşı, Hasan; Şit, Dede (The European Research Journal, 2023)
Objectives: In this study, we aimed to research the frequency of musculoskeletal manifestations of patients receiving hemodialysis treatment, and evaluate the relationship between quality of life and musculoskeletal manifestations of these patients. Methods: Patients undergoing hemodialysis for at least 6 months were included in our study. Patients were asked to complete a questionnaire that formed by the investigators including demographic, clinical features, and musculoskeletal symptoms that frequently seen in patients who receive hemodialysis. Kidney Disease Quality of Life Short Form Version 1.3 (KDQOL-SF 1.3) and Short Form Health Survey (SF 36) questionnaires were completed by the patients and the control group. Blood urea nitrogen, serum creatinine, serum albumin, C-reactive protein (CRP), parathormone (PTH), ferritin, calcium, phosphate, hemoglobin, and Kt/V were measured. Also, the patients were divided into two subgroups according to musculoskeletal symptoms and these subgroups were compared in terms of dialysis adequacy, quality of life scoring and laboratory findings. Results: Seventy-four patients (42 males, 32 females) were enrolled in our study. The mean age of the patients was 60.85 ± 12.29 years. Six-five (87.83%) patients had musculoskeletal symptoms. There was statistically major difference in terms of smoking between subgroups (p = 0.046). We did not detect any correlation between two groups in terms of Kt/V (p = 0.411). Pain in shoulder/neck (41.9%), pain in limbs (58.1%) and pain in back (56.8%) were the most detected musculoskeletal symptoms of the patients. There was statistically significant difference between genders in terms of joint swelling, muscle cramps, pain in limbs, back and neck /shoulder (p = 0.015, p = 0.001, p = 0.008, p = 0.001, and p = 0.004, respectively). We detected that all subunits of KDQOL scores were higher in control group than patients who were included in our study. There was statistically significant relation between emotional role and energy subunits of KDQOL scores and CRP (p = 0.031 and p = 0.025, respectively). Conclusion: The results of our study were not as significant as the results of similar studies, however they are valuable because they show demographic, clinical characteristics, and quality of life of patients receiving hemodialysis in our region.